2013
DOI: 10.1128/jcm.01224-13
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Gram-Positive Organisms by Use of the Verigene Gram-Positive Blood Culture Nucleic Acid Test and the BacT/Alert Pediatric FAN System in a Multicenter Pediatric Evaluation

Abstract: Assays that expedite the reporting of organism identification and antibiotic susceptibility status in positive blood cultures can fast track interventions that improve clinical outcomes. We evaluated the Verigene Gram-positive blood culture nucleic acid test (BC-GP) in two pediatric hospitals. Positive BacT/Alert Pediatric FAN blood cultures with Gram-positive organisms were tested using the BC-GP in tandem with routine laboratory procedures. To test organisms underrepresented in the clinical blood culture eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 20 publications
(24 reference statements)
1
43
0
Order By: Relevance
“…Four recent studies have evaluated the performance of the BC-GP assay on different bottle types (12)(13)(14)(15). Specifically, Sullivan et al reported high sensitivity and specificity in pediatric patients using BacT/Alert pediatric FAN (PF) blood cultures (14).…”
mentioning
confidence: 99%
“…Four recent studies have evaluated the performance of the BC-GP assay on different bottle types (12)(13)(14)(15). Specifically, Sullivan et al reported high sensitivity and specificity in pediatric patients using BacT/Alert pediatric FAN (PF) blood cultures (14).…”
mentioning
confidence: 99%
“…Several papers have already evaluated the Verigene panel dedicated to Gram-positive bacteria (8)(9)(10)(11)(12), but this is the first one on the BC-GN test. To investigate its potential clinical usefulness, we evaluated the following parameters: (i) the concordance of identification and of antibiotic susceptibility data with those obtained with the traditional blood culture flowchart, (ii) the time to definitive results, and (iii) the impact of the BC-GN test results on ongoing empirical therapy, evidencing the rate of potential BC-GN-induced antibiotic changes.…”
mentioning
confidence: 99%
“…There were no discordant results encountered between the BC-GP and MicroScan Walkaway systems. Although the overall number of SAG isolates included in previous evaluations of the Verigence BC-GP system was low, the majority of reports have also observed 100 % accuracy for this group (Beal et al, 2013; Sullivan et al, 2013). Species identification and characterization of haemolysis were able to be performed on 31 of the 34 SAG isolates.…”
Section: Microbiology and Antimicrobial Susceptibilitymentioning
confidence: 89%